2021
DOI: 10.1038/s41467-021-24997-7
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasites both repress host CXCL10 and use it as a cue for growth acceleration

Abstract: Pathogens are thought to use host molecular cues to control when to initiate life-cycle transitions, but these signals are mostly unknown, particularly for the parasitic disease malaria caused by Plasmodium falciparum. The chemokine CXCL10 is present at high levels in fatal cases of cerebral malaria patients, but is reduced in patients who survive and do not have complications. Here we show a Pf ‘decision-sensing-system’ controlled by CXCL10 concentration. High CXCL10 expression prompts P. falciparum to initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 97 publications
(147 reference statements)
2
30
0
Order By: Relevance
“…EVs were concentrated using a Vivacell (Ofir-Birin et al, 2021), third of the EV sample was treated with 10 μl/ml Sialidase (Neuraminidase, REF 11080752001, LOT 1005025, Roche). The solution was incubated for 30 min at 37 • C. The remaining two thirds of the EV sample were used as control and were incubated for 30 min at 37 • C. The EV production proceeded to TO staining and an overnight ultracentrifugation step (Sisquella et al, 2017).…”
Section:  Sialidase Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs were concentrated using a Vivacell (Ofir-Birin et al, 2021), third of the EV sample was treated with 10 μl/ml Sialidase (Neuraminidase, REF 11080752001, LOT 1005025, Roche). The solution was incubated for 30 min at 37 • C. The remaining two thirds of the EV sample were used as control and were incubated for 30 min at 37 • C. The EV production proceeded to TO staining and an overnight ultracentrifugation step (Sisquella et al, 2017).…”
Section:  Sialidase Treatmentmentioning
confidence: 99%
“…Extracellular Vesicles (EVs) are produced across almost all the living kingdoms (Carrera-Bravo et al, 2021;Malda et al, 2016;Osteikoetxea et al, 2016;Pegtel et al, 2010;Schorey et al, 2015;Wortzel et al, 2019) including parasites (Carrera-Bravo et al, 2021;Montaner et al, 2014;Ofir-Birin & Regev-Rudzki, 2019). They contain a cornucopia of different molecules and transfer functional signals to target cells.…”
Section: Introductionmentioning
confidence: 99%
“…One such prominent example is the deadly malaria parasite in humans, Plasmodium falciparum ( Pf ). During their life-cycle, Pf parasites secrete EVs while growing inside human red blood cells (RBCs), which deliver multiple cargo components ( Regev-Rudzki et al., 2013 ; Mantel et al., 2016 ; Sisquella et al., 2017 ; Ye et al., 2018 ; Avalos-Padilla et al, 2021 ; Dekel et al., 2021 ; Ofir-Birin et al., 2021 ). These EVs modulate different host cells by promoting parasitic invasion ( Dekel et al., 2021 ), endothelial cell modulation ( Mantel et al., 2016 ) and immune cell alteration ( Mantel et al., 2013 ; Sisquella et al., 2017 ; Ye et al., 2018 ; Ofir-Birin et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During their life-cycle, Pf parasites secrete EVs while growing inside human red blood cells (RBCs), which deliver multiple cargo components ( Regev-Rudzki et al., 2013 ; Mantel et al., 2016 ; Sisquella et al., 2017 ; Ye et al., 2018 ; Avalos-Padilla et al, 2021 ; Dekel et al., 2021 ; Ofir-Birin et al., 2021 ). These EVs modulate different host cells by promoting parasitic invasion ( Dekel et al., 2021 ), endothelial cell modulation ( Mantel et al., 2016 ) and immune cell alteration ( Mantel et al., 2013 ; Sisquella et al., 2017 ; Ye et al., 2018 ; Ofir-Birin et al., 2021 ). For instance, it was shown that Pf -derived EVs deliver parasitic genomic DNA (gDNA), recognized by the STING-dependent cytosolic DNA sensing pathway in recipient monocytes ( Sisquella et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to their role in parasite-parasite communication, EVs have potent immunoregulatory properties. For instance, EVs can stimulate monocytes and macrophages to secrete proinflammatory cytokines and chemokines ( Couper et al, 2010 ; Sisquella et al, 2017 ; Mbagwu et al, 2019 ; Ofir-Birin et al, 2021 ). EVs secreted by mast cells worsen the development of cerebral malaria in the rodent malaria ( Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%